Machine-learning models for predicting CO2 solubility in various brine systems: implications for carbon geo-storage; Journal of Molecular Liquids; Vol. 435 - Davoodi Sh. Shadfar; Longe P. O. Promise; Hung Vo Thanh; Mehrad M. Mohammad; Mohammadi A. H. Amir; Burnaev E. Evgeny (2025, 2025)
Title screen